(y 1/3)(y-1/3)

Question

Asked 11/17/2014 7:10:05 AM

Updated 12/4/2014 10:16:59 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [12/4/2014 10:16:34 PM]

s

rugmaker|Points 3544|

rugmaker|Points 3544|

= 4[(5) + 3(3)];

= 4(5 + 9);

= 4 * 14;

= 56

stickman|Points 6262|

= 16y^2a^2 + 24yaxb - 24yaxb - 36x^2b^2;

= 16y^2a^2 - 36x^2b^2;

= 16a^2y^2 - 36b^2x^2

jeifunk|Points 36944|

Question

Asked 11/17/2014 7:10:05 AM

Updated 12/4/2014 10:16:59 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [12/4/2014 10:16:34 PM]

Rating

8

(a + b - c)(a + b + c)

= (a + b)^2 - c^2

= a^2 + 2ab + b^2 - c^2

= (a + b)^2 - c^2

= a^2 + 2ab + b^2 - c^2

Added 12/4/2014 10:16:17 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [12/4/2014 10:40:55 PM]

8

(x + y)(x^2 - xy + y^2) = x^3 + y^3

Added 12/4/2014 10:16:59 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [12/4/2014 10:41:26 PM]

34,464,312

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 804 [Total 6677] Ratings 19 Comments 614 Invitations 0 Offline

There are no comments.